Validation of contemporary electrocardiographic indices of area at risk and infarct size in acute ST elevation myocardial infarction (STEMI). (15th March 2020) - Du, Yang Timothy; Pasupathy, Sivabaskari; Air, Tracy; Neil, Christopher; Beltrame, John F.
Abstract: Background: Electrocardiographic (ECG) methods to assess area at risk (AAR) and infarct size (IS) in patients with ST-elevation myocardial infarction (STEMI) have been previously established but not validated against contemporary benchmark Cardiac Magnetic Resonance (CMR) measures. We compared ECG-determined and CMR-determined measures for (a) AAR, (b) IS, and (c) myocardial salvage. Methods: Sixty patients with ECG evidence of STEMI and CMR imaging performed within 13 days were included. The ECG-determined (a) AAR scores (Aldrich and Wilkins), (b) IS (Selvester score), and (c) myocardial salvage (i.e. [AAR-IS] / AAR × 100%), were compared with CMR-determined measures. Results: Compared with CMR-determined AAR, both the Wilkins & Aldrich scores underestimated AAR, although the Wilkins (r = 0.72, p < 0.001) showed a better correlation than the Aldrich (r = 0.54, p < 0.001). Bland-Altman analysis revealed a bias of 2.6% (95% limits of agreement: 18.5%, −13.3%) for the Wilkins and 5.9% (95% limits of agreement: 25.6%, −13.8%) for the Aldrich. Estimation of IS was similar between the Selvester score and CMR, with good correlation (r = 0.77, p < 0.001) and agreement (fixed bias 0.4%, 95% limits of agreement 20.8%, −15.5%). However, ECG-determined myocardial salvage significantly underestimated CMR-determined myocardial salvage, with an inverse correlation (r = −0.33, p = 0.01). Conclusions: The Wilkins score is superior to Aldrich score as an ECG-AAR index, Selvester score is a reasonable ECG estimate of infarct size, though ECG derived myocardial salvage does not have enough accuracy to be used in the clinical setting; it may be an inexpensive surrogate for myocardial salvage in large research studies. Further validation and prognostic studies are required.